Inhibitory effects of the crude extract from Xylaria sp. on several pathogenic fungi - Azizi, Nurul Asyiqin (2019)
The genus Xylaria belongs to the phylum Ascomycota from the kingdom Fungi. A majority of the Xylaria species are known plant endophytes. Some have properties against phytopathogenic fungi, however, scientific evidence on the presence of the active compounds in Xylaria spp. is limited. Here, the inhibitory effects of an isolate of Xylaria sp. were demonstrated against three species of phytopathogenic fungi. Xylaria sp. crude extract (XCE) was obtained from a 14-day Potato Dextrose Broth (PDB) culture using ethyl acetate (EtOAc) as solvent. Non-volatile assays revealed that the XCE had the strongest inhibitory effect on the growth of Ceratocystis fimbriata from 79% to 100% rate of antifungal activity (AFA), followed by Fusarium oxysporum, 26% to 53%. There was little to no inhibition against Phellinus noxius. The XCE was further purified using a silica gel column yielding six different eluents (XH, XHD, XD, XDM, XMH, XM) and tested against Ceratocystis fimbriata in disc-diffusion assay. XH gave the highest average AFA (26%), followed by XDM (21%), while the other eluents exerted between 9% to 17% inhibition. Further studies should identify the potential compounds in XH against C. fimbriata.